(Dimesityl)boron Benzodithiophenes: Synthesis, Electrochemical, Photophysical and Theoretical Characterization. Issue 1 (21st January 2022) - Menduti, Luigi; Baldoli, Clara; Arnaboldi, Serena; Dreuw, Andreas; Tahaoglu, Duygu; Bossi, Alberto; Licandro, Emanuela
Abstract: Triarylboranes containing linear or angular benzodithiophene moieties and bearing one or two dimesitylboron units were synthesized. The electrochemical and optical features of these compounds were investigated by cyclic voltammetry, UV/Vis and fluorescence spectroscopy while DFT calculations were run to analyze the energetic landscape of these systems. For both linear and angular benzodithiophenes, symmetrical disubstitution leads to the highest photoluminescence yields. The linear benzodithiophene disubstituted with two dimesitylboron units proved to be the most interesting and promising molecule as an electron‐transport material for organic electronics owing to its LUMO energy level of −2.84 eV which is close to those of commonly used electron transport materials like bathocuproine or bathophenantroline. Abstract : Functionalization of benzodithiophenes with (dimesityl)boryl moieties provided derivatives with remarkable electrochemical and spectroscopic properties. The introduction of two boryl groups on the linear benzodithiophene yielded a stable blue‐emitter with high potential as electron‐transport material and naked‐eye fluorescence turn‐off sensor.